PENGARUH PERPUTARAN MODAL KERJA TERHADAP CURRENT RATIO PADA PT ANEKA TAMBANG TBK SELAMA PERIODE 2006 – 2014 - Atikah Anisah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Devined working capital turnover ratio used to measure how many times the funds invested in working capital spins in one period. The current ratiois the ratio used to measure a company’s ability to meet short-term obligations without facing any difficulty. And his purpose in this study to determin the development and influence of rotation of working capital and current ratio at PT. Aneka Tambang (Persero) Tbk. Simple linear regression equation can be interpreted as follows Y = 5,231 + 8,583 X. positive coefficient value shows a positive effect on working capital turnover against the current ratio in PT. Aneka Tambang Tbk. If the value of working capital turnover increased by one percent, the value of the current ratio increases by 8,583%. Coefficient of determination R² obtained to 0,164. This number denotes that the variable working capital turnover explain the variable current ratio at PT. Aneka Tambang (Persero) Tbk. By 16,4% while the remaning 83,6% is influenced by other factor beyond research. Based on the test results is known that there is no significant effect of variable worming capital turnover against the current ratio at PT. Aneka Tambang. The period 2006 to 2014. To obtain a good current ratio according to the target, but the company’s good watch on the working capital turnover adjusted for the company’s activities. So it can be used effectively and efficiently.Keyword: working capital turnover, current ratio